Preparation Activated Carbon from Scrap Tires by Microwave Assisted KOH Activation for Removal Emulsified Oil - Majeed, Najwa Saber; Sabbar, Huda Adil; Al-Musawi, Nawar O. A. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
In this paper activated carbon adsorbents produced from waste tires by chemical activation methods and application of microwave assisted KOH activation. The influence of radiation time, radiation power, and impregnation ratio on the yield and oil removal which is one of the major environmental issues nowadays and considered persistent environmental contaminants and many of them are suspected of being carcinogenic. Based on Box-Wilson central composite design, polynomial models were developed to correlate the process variables to the two responses. From the analysis of variance the significant variables on each response were identified.  Optimum conditions of 4 min radiation time, 700 W radiation power and 0.5 g/g impregnation ratio gave 205.8749 mg/g oil removal and 35.19618 % yield. The characteristics of the AC were examined by pore structure analysis, and scanning electron microscopy (SEM).The BET surface area and total pore volume were identified to be 374.594 m²/g and 0.2039 m³/g, respectively.